Characterization of orange-spotted grouper (Epinephelus coioides) ASC and caspase-1 involved in extracellular ATP-mediated immune signaling in fish. Issue 97 (February 2020) - Zhang, Xin; Liu, Zetian; Li, Chen; Zhang, Ya; Wang, Liqun; Wei, Jingguang; Qin, Qiwei
Abstract: Apoptosis-associated speck-like protein containing a CARD domain (ASC) is a critical adaptor molecule in multiple inflammasome protein complexes that mediate inflammation and host defense. Caspase-1 is a member of inflammatory caspases that play important roles in the innate immune system. However, few studies have been performed in lower vertebrates such as teleosts and implications of extracellular ATP-mediated immune signalling in fish. Here we identified and characterized novel ASC and caspase-1 genes (namely EcASC and EcCaspase-1 ) from the orange-spotted grouper (Epinephelus coioides ). EcASC and EcCaspase-1 encode 204- and 388-aa proteins which shared 55.34% and 72.89% identity with those in Siniperca chuatsi and Perca flavescens, respectively. EcASC contained a PYRIN domain (aa 5–82) and CARD domain (aa 107–201). EcCaspase1 contained a CARD domain (aa 1–88) and a CASc domain (aa 127–376). Both EcASC and EcCaspase-1 were distributed in all tissues tested in the healthy grouper. The expression of EcASC and EcCaspase-1 was significantly upregulated in response to ATP infection. Subcellular localization analysis showed that EcCaspase-1 exhibited a clear distribution in both cytoplasm and nucleus. In contrast, EcASC was observed in the cytoplasm as speck-like structures, which are called "pyroptosomes". EcCaspase-1 co-localized with the spot-like protein (EcASC). Overexpression of EcASC and EcCaspase-1 inhibited NF-κB activation and promoted P53 activation in grouper spleen (GS) cells. Extracellular ATP was an effective signaling molecule that activates the innate immune response, rapidly upregulating the expression of EcASC and EcCaspase1, and enhancing their promotion of proinflammatory cytokine expression in GS cells. Both EcASC and EcCaspase-1 promoted ATP-induced apoptosis. Our results suggested that the interactions of inflammatory EcCaspase-1 with EcASC proteins were associated with extracellular ATP-mediated immune signaling in fish. Highlights: Both EcASC and EcCaspase-1 are distributed in all tissues tested in the healthy grouper. EcCaspase-1 exhibited a different distribution with EcASC. EcCaspase-1 co-localized with the spot-like protein (EcASC). Both EcASC and EcCaspase-1 promoted ATP-induced apoptosis.